The Good, the Bad, and the Legal: Lawyering in China’s Wild West - Wu, Peng (Columbia Journal of Asian Law, 2008)
The explosive growth of legal professionals in China over the past two decades is unprecedented in history, but geographically the growth has also been wildly uneven. After the Cultural Revolution in the late 1970s, the country had about 3000 lawyers, most of whom had just suffered severe social and political persecution. Today, China has approximately 150,000 lawyers. However, one-third of them are concentrated in Beijing, Shanghai, Jiangsu, Guangdong, and Zhejiang, and they account for two-thirds of the national income earned by lawyers. By contrast, over 200 rural counties in China do not have a single lawyer. The earnings of the 400 to 500 lawyers in Qinghai, an undeveloped province on the northeastern portion of the Tibetan Plateau, make up 0.12% of the national lawyerly income. While the numbers are startling, the situation of lawyers in China cannot be told by numbers alone. Commentators on China’s development sometimes assume that more lawyers equals more justice, because more laobaixing (a colloquial term for the average person or peasant) will have access to the legal system through which they can air their grievances. Michelson’s empirical research on case-screening methods used by lawyers in a Beijing law firm when faced with workers who have labor grievances has challenged the simplicity of this assumption. However, beyond the usual statistics lamenting the paucity of lawyers, there has been very little in-depth research on the practice of law in China’s less developed regions in the west. Given the reality of China’s uneven economic development and the increasing gap between urban and rural areas, a better understanding of the bar beyond the prosperous regions of the east coast seems vital in order to gain a more complete picture of China’s legal development. The goal of this paper is to provide the beginnings of some insight into what has been a largely neglected area. First, I will give an overview of the bar in Xining, the capital of Qinghai, and highlight some of the issues facing legal professionals in China’s undeveloped regions. In this section, I cover the structure of law firms in Xining, the practice of an average lawyer, and the issue of emigration out of Qinghai to major cities in the east. Second, I hope to show that the emerging professional identity that the interviews reveal is complex and contains many contradictions. This is most apparent in the lawyers’ attitudes towards basic-level legal workers (基法工者another group of legal professionals established 层律作), by the government in the 1980s to perform simple legal and administrative tasks in rural areas where lawyers were scarce.5 In recent years, legal workers, just like other Chinese, have migrated to urban centers, and lawyers feel threatened by their encroachment on the lawyer’s professional turf. At the same time, lawyers in Xining take pride in their distinction from legal workers, and refuse those cases perceived to be beneath the dignity of a lawyer and more suitable for a legal worker. Against this background, I argue that legal workers are playing a valuable role even in urban centers in terms of taking up cases that lawyers do not want. Furthermore, the notion that simply increasing the number of lawyers in rural regions will lead to improved access to justice for laobaixing and better rule of law is both simplistic and misguided.